The potential of phage therapy in cystic fibrosis: Essential human-bacterial-phage interactions and delivery considerations for use in Pseudomonas aeruginosa-infected airways - Trend, S.; Fonceca, A.; Ditcham, W.; Kicic, Anthony; AREST CF (Elsevier, 2017)
As antimicrobial-resistant microbes become increasingly common and a significant global issue, novel approaches to treating these infections particularly in those at high risk are required. This is evident in people with cystic fibrosis (CF), who suffer from chronic airway infection caused by antibiotic resistant bacteria, typically Pseudomonas aeruginosa. One option is bacteriophage (phage) therapy, which utilises the natural predation of phage viruses upon their host bacteria. This review summarises the essential and unique aspects of the phage-microbe-human lung interactions in CF that must be addressed to successfully develop and deliver phage to CF airways. The current evidence regarding phage biology, phage-bacterial interactions, potential airway immune responses to phages, previous use of phages in humans and method of phage delivery to the lung are also summarised. © 2017 European Cystic Fibrosis Society.